Local Platelet-rich plasma (PRP) injection for the treatment of Delayed Union after Internal Fixation in Fractures of Long Bones - Prasai, Tanup; Sharma, Sashmit; Rijal, Kiran Prasad; Khanal, Krishna Raj (Journal of Society of Surgeons of Nepal, 2020)
Introduction: Long bone fractures are among the most common orthopaedic injuries encountered. A fracture that fails to progress to union despite appropriate fixation and absence of complications presents a treatment dilemma to the surgeon. The usual solution of re-fixation with or without bone graft constitutes repeat exposure to surgery and its risks, as well as added morbidity and cost. Recent advances in molecular biology suggest Platelet rich plasma (PRP) may have bone forming potential. This study was done to determine whether PRP has any beneficial role in patients with delayed healing of long bone fractures. Methods: A prospective interventional study was done on patients arriving at the department of orthopaedic surgery of Kathmandu Medical College with delayed union of long bone fractures after internal fixation between January 2014 and January 2017. Patients were treated with local injection of group-matched PRP directly into the fracture gap and were followed-up for six months to check for radiological signs of fracture union. Results: A total of 10 fractures were included in 10 patients that involved four humeri, three tibiae, and three femora. Eight out of the 10 fractures united at a median time of three months after the injection. Two had non-union that required revision surgery. Conclusion: Local Platelet rich plasma injection may constitute a ‘nothing to lose, everything to gain’ intermediate option before a decision for major reoperation on such patients is made.